Response of Human Immunodeficiency Virus-Associated Cerebral Angiitis to the Combined Antiretroviral Therapy - Cheron, Julian; Wyndham-Thomas, Chloé; Sadeghi, Niloufar; Naeije, Gilles (Frontiers in Neurology, 2017)
When secondary causes are excluded, mechanisms underlying central nervous system angiitis (ACNS) in HIV-infected patients are still not understood and optimal treatment remains undefined. We report here a patient with an untreated HIV-infection who presented multiple ischemic strokes probably due to HIV-ACNS. ACNS signs on vessel-wall imaging magnetic resonance monitoring retracted with combined antiretroviral therapy without adjunct immunosuppressive drugs.